2009
DOI: 10.1016/s1875-9572(09)60033-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Analysis of Influenza B Infection in Children in Taichung, Taiwan during the 2006-2007 Flu Season

Abstract: Most children who contracted influenza B infection had not been vaccinated. Almost half the children had leukopenia, and some had leukocytosis, but thrombocytopenia was rare. There was a significant association between raised CK levels and myalgia in influenza B infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…One of the biological factors that had been reported to influence antigenicity is the glycosylation patterns of HA. 31 , 32 However, we found no obvious association between the number of potential glycosylation sites on the different HAs we tested here with the pattern of antibody responses we observed. 33 , 34 Barring these and subtype-specific differences, the other distinguishing feature between the HA of avian- and human-origin influenza viruses is the receptor-binding specificity.…”
Section: Discussioncontrasting
confidence: 57%
“…One of the biological factors that had been reported to influence antigenicity is the glycosylation patterns of HA. 31 , 32 However, we found no obvious association between the number of potential glycosylation sites on the different HAs we tested here with the pattern of antibody responses we observed. 33 , 34 Barring these and subtype-specific differences, the other distinguishing feature between the HA of avian- and human-origin influenza viruses is the receptor-binding specificity.…”
Section: Discussioncontrasting
confidence: 57%
“…We found no association between myalgias and CK values. Eleven of the patients (84.6%) with elevated CK levels, compared with only four (40%) of the patients with normal CK levels had myalgia 11 . No case of rhabdomyolysis was observed.…”
Section: A C C E P T E Dmentioning
confidence: 94%
“…Pulmonary complications such as primary viral pneumonia, secondary bacterial or fungal pneumonia, combined viral-bacterial pneumonia, and exacerbations of chronic pulmonary diseases have been described (Aebi et al, 2010; Chen et al, 2011; Gutierrez-Pizarraya et al, 2012; Krell et al, 2003; Paddock et al, 2012; Wang et al, 2009; Yusuf et al, 2007). Importantly, histological evidence of interstitial pneumonia and immunohistochemical features of alveoli involvements during influenza B virus infections was provided for fatal cases (Paddock et al, 2012).…”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%
“…This study also found that bacterial superinfections were more common in patients over 18 (Paddock et al, 2012). Several single-patient reports of severe influenza B suggested complication with acute respiratory distress syndrome (Cardoso et al, 2012; Lu et al, 2004; Namendys-Silva et al, 2011; Wang et al, 2009). …”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%